A distributed implementation of Structured Gamma - Paillard, G.A.L.; Franca, F.M.G.; Filho, J.A.M. (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
Presents a distributed implementation of the Structured Gamma programming language, a language based on the Gamma multi-set rewriting paradigm. Structured Gamma offers, in addition to the advantages introduced by Gamma, implicit concurrent behavior and a type system where not only types themselves are defined but also the automatic verification of user-defined types at compilation time. The problems and mechanisms involved in an MPI-based implementation of Structured Gamma using a type-checking engine based on the most general unifier (MGU) are investigated.